Comparative genomics reveals the in planta‐secreted Verticillium dahliae Av2 effector protein recognized in tomato plants that carry the V2 resistance locus. (29th October 2020) - Chavarro‐Carrero, Edgar A.; Vermeulen, Jasper P.; E. Torres, David; Usami, Toshiyuki; Schouten, Henk J.; Bai, Yuling; Seidl, Michael F.; Thomma, Bart P. H. J.
Summary: Plant pathogens secrete effector molecules during host invasion to promote colonization. However, some of these effectors become recognized by host receptors to mount a defence response and establish immunity . Recently, a novel resistance was identified in wild tomato, mediated by the single dominant V2 locus, to control strains of the soil‐borne vascular wilt fungus Verticillium dahliae that belong to race 2 . With comparative genomics of race 2 strains and resistance‐breaking race 3 strains, we identified the avirulence effector that activates V2 resistance, termed Av2 . We identified 277 kb of race 2‐specific sequence comprising only two genes encoding predicted secreted proteins that are expressed during tomato colonization. Subsequent functional analysis based on genetic complementation into race 3 isolates and targeted deletion from the race 1 isolate JR2 and race 2 isolate TO22 confirmed that one of the two candidates encodes the avirulence effector Av2 that is recognized in V2 tomato plants. Two Av2 allelic variants were identified that encode Av2 variants that differ by a single acid. Thus far, a role in virulence could not be demonstrated for either of the two variants.